PENGARUH MODEL SIKLUS BELAJAR 5E (Engagemant, Exploration, Explanation, Elaboration, Evaluation) TERHADAP KEMAMPUAN APLIKASI KONSEP SISWA PADA MATERI SISTEM SARAF - Andra Rian Mulyna; tuti kurniati; tri wahyu agustina (Department of Biology Education UIN Sunan Gunung Djati Bandung, 2017)
This research supported by the problems emerging in class xi mia sman 27 bandungbecause less increasing study results in learning biology students. To overcome theseproblems by using a learning process implemented learning model learning cycle5E. Thisstudy aimed to determine the effect of the Learning Cycle 5E model of application of theconcept of students' abilities in the material of the nervous system as well as knowingketerlaksanaan process of learning by using learning model 5E learning cycle on the materialof the nervous system.The method used is Quasi-Experimental Design with a sample that isclass I and class XI XI MIA MIA II the number of students in each class of 30 students. Thesampling technique used was purposive sampling. Research instrument used was a set of testsand observation sheet. Analysis of study data including normality test, homogeneity test andtest hypotheses.Results of analysis keterlaksanaan learning process by using the learningcycle 5E model of the average values obtained 97.50% berkategorikan good enough for theactivities of teachers and 96% berkategorikan good enough for the student activity. Theresults showed that the application of the concept of students' ability to use the learning cycle5E learning model obtained an average value of 44.56 initial test, the final test of 72.17, NGainof 0.50 berkategorikan being an indicator of high concept application that indicatorapplication of the material that has been learned within the family, school, community.Application of the concept of students' abilities without using 5E learning cycle modelobtained an average value of 43.31 initial test, the final test 55.26, N 0.21 Gainberkategorikan-low, high-concept application indicators are indicators of the application ofthe material that has been studied in the environment family, school, community. Hypothesistest results at the end of the test Learning Cycle 5E learning model on the nervous systemmaterial obtained t 5.06> 1.69 ttable at significance level of 5%. Based on the results of thisstudy concluded that there are significant learning model Learning Cycle 5E on the ability ofthe students expressed significant application of concepts and hypotheses accepted.